PERKEMBANGAN BENGKEL SEPEDA MOTOR DI KECAMATAN PADANG UTARA KOTA PADANG TAHUN 2000-2019 - Yesryl Nela Frendos; Ahyuni Ahyuni (JURNAL BUANA, 2020)
This research was conducted in the North Padang District which aims to look at the characteristics of the motorcycle repair shop business, see how the distribution pattern of the motorcycle business and see how the development of a motorcycle business in the North Padang District in 2000-2019. The method used in this research is descriptive quantitative approach and the data used are primary data. The results were obtained from interviews and questionnaires and taking the coordinates. The characteristics of a motorcycle repair shop business in Padang Utara District can be seen from the capital, income, labor and service hours or working hours. The average capital of a motorcycle repair shop business in Padang Utara District is 8,000,000.00 rupiahs with an average income of 5,000,000.00-10,000,000.00 rupiahs with an average workforce of 2 people and with 10 service hours opening hours are 09.00-18.00 WIB. The distribution pattern of motorcycle repair shops in Padang Utara District, Padang City is a clustered pattern. The development of a motorcycle repair shop business in Padang Utara District, Padang City from 2000 - 2019, was seen from the year of its founding there were 39 workshops spread throughout the Kelurahan in Padang Utara District.